Triumph of the yuppies : America, the eighties, and the creation of an unequal nation - McGrath, Tom (Grand Central Publishing, 2024)
"The first history fo the Yuppie phenomenon, chronicling the roots, rise, triumph, and (seeming) fall of the "young urban professionals" who radically altered American life between 1980 and 1987."--Dust jacket flap.